2013
DOI: 10.1172/jci70510
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty-2 regulates HIV-specific T cell polyfunctionality

Abstract: The ability of individual T cells to perform multiple effector functions is crucial for protective immunity against viruses and cancer. This polyfunctionality is frequently lost during chronic infections; however, the molecular mechanisms driving T cell polyfunctionality are poorly understood. We found that human T cells stimulated by a high concentration of antigen lacked polyfunctionality and expressed a transcription profile similar to that of exhausted T cells. One specific pathway implicated by the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 50 publications
(69 reference statements)
3
34
0
Order By: Relevance
“…It is anyway difficult to draw firm conclusions, because most T-cell recognition analyses in Linnemann and colleagues (11) were performed with autologous B cells (presenting neoantigens) as targets and not tumor cells. It is indeed known from previous studies that several factors can affect T-cell functionality, including antigen density (38,39) that may of course be different in peptide-loaded APCs and tumor cells. Future studies will determine whether functional differences exist between CD4 þ T-cell subsets specific to different classes of tumor antigens.…”
Section: Discussionmentioning
confidence: 99%
“…It is anyway difficult to draw firm conclusions, because most T-cell recognition analyses in Linnemann and colleagues (11) were performed with autologous B cells (presenting neoantigens) as targets and not tumor cells. It is indeed known from previous studies that several factors can affect T-cell functionality, including antigen density (38,39) that may of course be different in peptide-loaded APCs and tumor cells. Future studies will determine whether functional differences exist between CD4 þ T-cell subsets specific to different classes of tumor antigens.…”
Section: Discussionmentioning
confidence: 99%
“…c | Experiments using detailed antigen titration have also shown that the dissociation time determines both the potency (EC 50 ) and maximal efficacy (E max ), such that antigens with short dissociation times cannot produce the same maximal response as antigens with long dissociation times 6,13 . Recent data have also suggested the existence of an optimal antigen dose for T cell activation (not shown) 39,40 . Note that panels b and c are schematics.…”
Section: Phenotypic Modelsmentioning
confidence: 99%
“…3). There is some experimental evidence for an optimal antigen dose 24, 39,40 , but additional work with antigens of varying affinities is needed. (FIG.…”
Section: Digital Signallingmentioning
confidence: 99%
“…At least two mediators of TCR signals, SPRY2 and NFAT, have been identified as factors involved in supporting the establishment of exhaustion in CD8 ϩ T cells (25,26). Our data indicate that NFAT1 is also a central regulator of the induction of exhaustion in CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 61%